Can metabolic tightening and expansion of co-expression network play a role in stress response and tolerance?. (April 2020) - Fait, Aaron; Batushansky, Albert; Shrestha, Vivek; Yobi, Abou; Angelovici, Ruthie
Highlights: In this opinion piece, we discuss whether metabolic rearrangement of gene co-expression networks play a role in stress response in plants. We used a study case in Arabidopsis to demonstrate that metabolic networks tighten and expand in response to drought and heat stresses. However, more studies are needed to fully assess the metabolic network response to stress and its implications on plants stress tolerance. Abstract: Plants respond and adapt to changes in their environment by employing a wide variety of genetic, molecular, and biochemical mechanisms. When so doing, they trigger large-scale rearrangements at the metabolic and transcriptional levels. The dynamics and patterns of these rearrangements and how they govern a stress response is not clear. In this opinion, we discuss a plant's response to stress from the perspective of the metabolic gene co-expression network and its rearrangement upon stress. As a case study, we use publicly available expression data of Arabidopsis thaliana plants exposed to heat and drought stress to evaluate and compare the co-expression networks of metabolic genes. The analysis highlights that stress conditions can lead to metabolic tightening and expansion of the co-expression network. We argue that this rearrangement could play a role in a plant's response to stress and thus may be an additional tool to assess and understand stress tolerance/sensitivity. Additional studies are needed to evaluate the metabolic network in response to multiple stresses at various intensities and across different genetic backgrounds (e.g., intra- and inter-species, sensitive and tolerant eco/genotypes).